2009
DOI: 10.2478/s11756-009-0158-8
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and expression analysis of hsp70 gene from freshwater planarian Dugesia japonica

Abstract: Heat shock protein 70 (HSP70) is an important member of the heat shock protein family. It plays a key role in the process of protecting cells by facilitating the folding of nascent peptides as well as the cellular stress response. We isolated and sequenced a full-length HSP70 cDNA from planarian Dugesia japonica (designated Djhsp70) using rapid amplification of cDNA ends (RACE). Djhsp70 cDNA is highly homologous to other reported hsp70 family genes, and the deduced amino acid sequence shares several eukaryotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 37 publications
2
8
0
Order By: Relevance
“…Djhsp70 is an inducible gene, significantly up-regulated in response to temperature changes, amputation and starvation (Ma et al, 2009). Our whole mount in situ hybridizations demonstrated that Djhsp70 transcripts are widely distributed along the planarian body and up-regulated in the regenerative blastema (Fig.…”
Section: Hsp70 Genesmentioning
confidence: 74%
See 1 more Smart Citation
“…Djhsp70 is an inducible gene, significantly up-regulated in response to temperature changes, amputation and starvation (Ma et al, 2009). Our whole mount in situ hybridizations demonstrated that Djhsp70 transcripts are widely distributed along the planarian body and up-regulated in the regenerative blastema (Fig.…”
Section: Hsp70 Genesmentioning
confidence: 74%
“…Although our in silico search revealed that several hsp70-related genes are present in the planarian genome (not shown), only two different members of this family have been characterized so far: Djhsp70 and Djmot (Conte et al, 2009;Ma et al, 2009). Djhsp70 is an inducible gene, significantly up-regulated in response to temperature changes, amputation and starvation (Ma et al, 2009).…”
Section: Hsp70 Genesmentioning
confidence: 94%
“…Several authors have proposed the use of the absence of introns as a criterion for recognizing the inducible hsp70 isoforms (Günther & Walter ; Ma et al . ). However, this criterion should be used with caution given that an intronless cognate form of hsp70 was recently described in the giant freshwater prawn Macrobrachium rosenbergii (Crustacea: Decapoda) (Liu et al .…”
Section: Discussionmentioning
confidence: 97%
“…However, the acute thermal stress is lethal to planarians. To investigate heat-shock response, most studies focused on the expression pattern of heatshock proteins (Ma et al 2009(Ma et al , 2012Manchado et al 2008). In the present study, we selected ALP as an indicator to evaluate the effects of thermal stress on the plasma membrane.…”
Section: Resultsmentioning
confidence: 99%